KOMUNIKASI PERSUASIF HSE (HEALTH SAFETY AND ENVIRONMENT) DALAM MENINGKATKAN KESADARAN KESELAMATAN KERJA PADA PT. DIMAS DRILLINDO DURI – RIAU - Defrianto, Leo Vani; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In companies engaged in oil drilling, HSE (Health Safety and Environment) has a very important role, which the HSE is working to control and inform about safety in the work, so that employees understand what danger would threaten him and know how to cope with the work accident. But the fact is work accident still happened particularly in the limited liability company (PT) Dimas Drillindo Duri - Riau. This study aims to determine credibility, message, channel, feedback, securities, environmental and persuasive communication strategies whether can run well in increasing safety awareness in the PT. Dimas Drillindo Duri - Riau.This study used a qualitative research method. The subjects were employees of PT. Dimas Drillindo consisting of 15 people─selected using the technique porposisive. While the data obtained using three data collection techniques, ie observation, interviews, documentation. As well as using the technique of data validity, extension of participation, and the adequacy of reference.The results showed that persuasive communication HSE (Health Safety and Environment) can increase safety awareness in PT. Dimas Drillindo Duri – Riau by paying attention to the six elements of persuasive communication prior to the HSE made persuasion to employees. HSE in PT. Dimas Drillindo already has credibility, it can be seen by observing the appearance, control issues and has a certificate of K3 in the field of oil and gas─this lead the employees to pay higher attention to them. They creates heart-touching motivational messages, mind the channel in persuading either directly or using the media, and receiving advice from any employee and also look at the effect of persuasion in order to evaluate the the errors in previous persuation and also be selective to the environment that the persuation will take place, improper environmental conditions can affect the emotional of employees, such as giving a briefing about safety during the day and with the heat and fatigue conditions, thusmaking employees irritated and do not listen to what was the HSE said. In addition to the six elements,was also reinforced by the persuasive strategy that consists of three strategies that: The PsychodynamicStrategy, is through the approach by focusing on the emotional and cognitive factors of employees; TheMeaning Construction Strategy, is pay attention to the environmental factors that influence employeebehaviour; and The Mirror Strategy, is to manipulate a understanding of the mate, fortune and deathare things that have been determined Allah and predict the most familiar way of thinking used byemployees.